Cysteinyl-leukotrienes promote cutaneous Leishmaniasis control - Noronha, Letícia Paula Trajano; Martins, Monique Daiane Andrade; Castro-Junior, Archimedes Barbosa; Thorstenberg, Maria Luiza; Costa-Soares, Laís; Rangel, Thuany Prado; Carvalho-Gondim, Felipe; Rossi-Bergmann, Bartira; Savio, Luiz Eduardo Baggio; Canetti, Claudio de Azevedo; Coutinho-Silva, Robson (Frontiers in Cellular and Infection Microbiology, 2023)
Leishmaniasis is a neglected tropical parasitic disease with few approved medications. Cutaneous leishmaniasis (CL) is the most frequent form, responsible for 0.7 - 1.0 million new cases annually worldwide. Leukotrienes are lipid mediators of inflammation produced in response to cell damage or infection. They are subdivided into leukotriene B4 (LTB4) and cysteinyl leukotrienes LTC4 and LTD4 (Cys-LTs), depending on the enzyme responsible for their production. Recently, we showed that LTB4 could be a target for purinergic signaling controlling Leishmania amazonensis infection; however, the importance of Cys-LTs in the resolution of infection remained unknown. Mice infected with L. amazonensis are a model of CL infection and drug screening. We found that Cys-LTs control L. amazonensis infection in susceptible (BALB/c) and resistant (C57BL/6) mouse strains. In vitro, Cys-LTs significantly diminished the L. amazonensis infection index in peritoneal macrophages of BALB/c and C57BL/6 mice. In vivo, intralesional treatment with Cys-LTs reduced the lesion size and parasite loads in the infected footpads of C57BL/6 mice. The anti-leishmanial role of Cys-LTs depended on the purinergic P2X7 receptor, as infected cells lacking the receptor did not produce Cys-LTs in response to ATP. These findings suggest the therapeutic potential of LTB4 and Cys-LTs for CL treatment.